New vasorelaxant indole alkaloids, villocarines A-D from Uncaria villosa. - Matsuo, Hirotaka; Okamoto, Ryuichi; Zaima, Kazumasa; Hirasawa, Yusuke; Ismail, Intan Safinar; Lajis, Md. Nordin; Morita, Hiroshi (Elsevier, 2011)
Villocarines A–D (1–4), four new indole alkaloids have been isolated from the leaves of Uncaria villosa (Rubiaceae) and their structures were elucidated by 2D NMR methods and chemical correlations. Villocarine A (1) showed vasorelaxation activity against rat aortic ring and showed inhibition effect on vasocontraction of depolarized aorta with high concentration potassium, and also inhibition effect on phenylephrine (PE)-induced contraction in the presence of nicardipine in a Ca2+ concentration-dependent manner. The vasorelaxant effect by 1 might be attributed mainly to inhibition of calcium influx from extracellular space through voltage-dependent calcium channels (VDC) and/or receptor-operated Ca2+-channels (ROC), and also partly mediated through the increased release of NO from endothelial cells and opening of voltage-gated K+-channels.